2009
DOI: 10.1002/gepi.20433
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer segregation analyses using 4390 families from UK and Australian population‐based studies

Abstract: Familial aggregation of prostate cancer is likely to be due to multiple susceptibility loci, perhaps acting in conjunction with shared lifestyle risk factors. Models that assume a single mode of inheritance may be unrealistic. We analyzed genetic models of susceptibility to prostate cancer using segregation analysis of occurrence in families ascertained through population-based series totaling 4390 incident cases. We investigated major gene models (dominant, recessive, general, X-linked), polygenic models, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 49 publications
2
25
0
3
Order By: Relevance
“…Lifestyle and environmental related risk factors for prostate cancer have not been found yet. Similar to RLS prostate cancer is genetically complex and predisposition may be passed on through multiple common low-penetrance alleles in combination with lifestyle or environmental risk factors [27]. Taking recent findings from genetic and epidemiologic studies into account, the question arises [28] if prostate cancer and RLS share more common biological pathways than only low serum ferritin levels and/or anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle and environmental related risk factors for prostate cancer have not been found yet. Similar to RLS prostate cancer is genetically complex and predisposition may be passed on through multiple common low-penetrance alleles in combination with lifestyle or environmental risk factors [27]. Taking recent findings from genetic and epidemiologic studies into account, the question arises [28] if prostate cancer and RLS share more common biological pathways than only low serum ferritin levels and/or anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Zusammen mit den ebenfalls häufig betroffenen Brüdern (33,2%), Onkel (13,2%) und Großvätern (8,5%) stellen sie rund 95% aller Angehörigen mit PCA dar. Diese Zahlen decken sich weitgehend mit den Ergebnissen anderer Arbeitsgruppen, die das Verwandtschaftsverhältnis der erkrankten Familienmitglieder ermittelt haben [5,12].…”
Section: Diskussionunclassified
“…It is increasingly appreciated that lifestyle factors may contribute to an increased cancer risk [9,10], but to what extent they contribute to the increased familial risks reported for prostate, breast or colorectal cancer is not known. Segregation analyses in families have indicated that genetic factors are important contributors to the familial risk [11][12][13][14][15][16]. Twin studies have also shown a significant heritability for prostate, breast and colorectal cancer [17][18][19][20].…”
Section: Introductionmentioning
confidence: 96%
“…The most critical assumption in twin studies is that MZ and DZ twins show similarities because of the sharing of environmental factors, so that the difference in concordance rates between MZ and DZ twins is only a reflection of genetic factors [23]. Another possible avenue for studying whether genetic and family environmental factors have differential influences on the transmission of cancer is a follow-up study of a large sample of adoptees [12]. Studies of adoptees offer a unique opportunity to study the genetic transmission of cancer because adoptees do not grow up in their biological families [23].…”
Section: Introductionmentioning
confidence: 99%